Kajian Dalam Perspektif Filsafat Hukum Pada Implementasi Penerapan Diversi: Terhadap Penyelesaian Tindak Pidana Anak Di Tingkat Penuntutan - Ferdy Ardhany Ferdy; Herwin Sulistyowati Herwin (Fakultas Hukum Universitas Darul Ulum, 2024)
The philosophy of law is a part of the search that is studied in the sphere of philosophical scope. Philosophy is a systematic thinking activity that can only be satisfied with accepting the results arising from the thinking activity itself. Philosophy does not limit itself only to sensory, physical, psychological or spiritual symptoms. He also asks not only